(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
Considering the significance and impact of COVID-19 global pandemic to the global economy and education, ethics should be highlighted as a fundamental facet of technology related disciplines, and professional responsibilities need be taught in higher education. Introducing ethics to undergraduate engineering students is critical in order to develop professionals who will make important and consequential decisions and perform the best practices in the technology field. Therefore, undergraduate institutions should provide opportunities to students to acquire knowledge and skills about ethical principles that affect engineering practices. This essay addresses the history of engineering ethics education and some challenges in higher education institutions in the United States.